A Comparative Study of Conditioning for Kabaddi Players at Different Levels: Optimizing Conditioning for Kabaddi Players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This conditions program for the Kabaddi Player has been designed as a complete program for the whole year. Kabaddi is a rought game for the well-conditioned athlete.The Kabaddi player must work hard on conditioning twelve month a year. The exercise are divided into pre-season, and off-season program. To complete the conditioning of body for Kabaddi, the player must include something to players more strengths, speed, agility, flexibility, balance, endurance, coordination, courage and many other products of physical fitness. Kabaddi players, because of their size and the physical demands of the game, must work hard to maintain this type of physical condition.With the overlap of season today, we have very few athletes who complete in two sports in college or universities. This is an age of specialization and much more so in professional Kabaddi. Many Kabaddi coaches and players do not know how to condition the body for Kabaddi. Trainers can mark the exercises they want the players to be sure to do to strengthen old injuries.